Influence of knowledge management system on customer satisfaction index - an application study of CRM by offering performance enhancement for transmission. Issue 4 (23rd August 2021) - Ramesh, S.; Sivakumar, V.J.
This research signifies a unique approach in cultivating the customer relationship, influenced by the enhancement of 'fatigue life' for transmission shaft through knowledge management system (KMS). The continuous knowledge sharing of recent findings and advancements among internal customers is a critical phenomenon for better product performance and skill improvement of individuals. Subsequently, the impact on customer satisfaction is often neglected on product performance-related studies. Hence, in this paper, the correlation between product performance and knowledge enhancement of the internal customers after gaining knowledge of recent innovations in addition to accumulated knowledge through available theoretical explanations and cross functional data is studied through KM framework. The impact of KMS on customer relationship management (CRM) is validated by studying customer satisfaction on products. The correlation study is concluded that knowledge enhancement through continuous knowledge sharing of recent findings among internal customers improves their knowledge, product performance quality, and in-turn customer satisfaction. Also, the inter-relationship and contribution of each input factor is established through KMS.